The potential impact of glycine supplementation on the process of aging - Michalina Wójcikiewicz; Julia Kulbacka; Witold Czyż; Julia Kacperczyk; Karol Dziedzic; Marta Chuncia-Ileczko; Maciej Wojszczyk; Damian Zys; Piotr Pasek; Julia Ryniecka; Wiktor Czaja; Michał Krzciuk (Quality in Sport)
Aging is a multifactorial process characterized by the progressive loss of cellular integrity, metabolic flexibility, mitochondrial function, and the gradual accumulation of oxidative and inflammatory damage. These changes increase vulnerability to age-related disorders, including cardiovascular disease, neurodegenerative conditions, metabolic syndrome, and frailty. Glycine, the simplest amino acid, has recently gained attention as a potential nutritional and therapeutic intervention to modulate various pathways implicated in aging. Beyond its structural role in collagen and other proteins, glycine is a critical precursor for glutathione- an essential intracellular antioxidant- plays a role in neurotransmission, and is involved in the synthesis of heme, creatine, and bile acids. Emerging studies suggest that glycine supplementation may alleviate oxidative stress, dampen chronic low-grade inflammation, improve insulin sensitivity, enhance mitochondrial function, and even mimic aspects of methionine restriction- a dietary approach known to extend lifespan in animal models. These combined effects may help preserve physiological function, slow the onset of age-associated diseases, and promote healthspan. Nevertheless, the evidence base is still evolving; most current data derive from animal models, in vitro experiments, and limited human trials. Rigorous, long-term, randomized controlled studies are needed to identify optimal dosing, determine long-term safety, and clarify whether glycine can be strategically leveraged as an anti-aging nutrient. If confirmed, glycine’s safety, affordability, and accessibility may make it a compelling option for improving the quality of aging worldwide.